Smoking status, symptom significance and healthcare seeking with lung cancer symptoms in the Danish general population - Lisa Maria Sele Sætre; Kirubakaran Balasubramaniam; Jens Søndergaard; Dorte Ejg Jarbøl (npj Primary Care Respiratory Medicine)
Abstract This study analyses the associations between smoking status and perceived symptom significance (concern and influence on daily activity) among individuals with possible lung cancer symptoms and investigate the influence of symptom significance on healthcare seeking among individuals with different smoking status. A nationwide survey with 21,920 randomly selected individuals aged ≥40 years included questions about lung cancer symptoms, symptom concern and influence on daily activities, GP contact, and smoking status. Descriptive statistics and multivariable regression models were applied. Overall, individuals who currently smoked were more likely to perceive their lung cancer symptoms as significant, and individuals who reported high symptom significance were more likely to seek healthcare with both specific and non-specific symptoms. The significance of symptoms appeared to have less pronounced effect on prompting healthcare seeking among individuals with a history of current smoking. This implies that they may benefit from support and encouragement to seek care.